Phytochemical profiles and cytotoxicity evaluation of the ethanolic extract of Malpighia emarginata leaves: Potential for its therapeutic use - Dos Santos Souza, Renato Constantino; Ferreira, Rodrigo Augusto Cristóvão; Violla, Paula Reis; Iyomasa-Pilon, Melina; Balie, Mariana [UNESP]; Yoshikawa, Ariane Harumi; Girol, Ana Paula [UNESP] (CSIR-National Institute of Science Communication and Policy Research (NIScPR), 2024)
The search for new natural compounds with relevant therapeutic properties has increased in recent years. The objective of this study was to investigate the biological properties of the ethanolic extract of Malpighia emarginata leaves. For this, phytochemical assays, high-performance thin layer chromatography (HPTLC), high-performance liquid chromatography (HPLC), antioxidant activity analysis using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and cytotoxicity by hemolysis, and chorioallantoic membrane (CAM) studies were performed. Through qualitative analyses, phenolic compounds and alkaloids were identified, and by quantitative analyses, 92.52, 2.02, and 0.59 µg/mL were found for total flavonoids, total alkaloids, and total phenols, respectively. HPTLC showed the presence of the flavonoids catechin and gallic acid, while HPLC identified myricetin and quercetin. The extract showed a high antioxidant capacity of 80.77% by DPPH. Moreover, low cytotoxicity of the extract at 10% was observed by hemolysis and CAM assay. Our results indicate that the ethanolic extract of M. emarginata leaves is a potential candidate for therapeutic use due to the presence of important bioactive compounds, high antioxidant activity and low cytotoxicity.
Keywords: Acerola; Alcoholic extract; DPPH; HPLC; HPTLC; Phytochemical compounds